PENGARUH IKLIM KOMUNIKASI ORGANISASI DAN WORK MEANINGFULNESS TERHADAP KOMITMEN ORGANISASI TENAGA KEPENDIDIKAN UNY DI MASA PANDEMI COVID-19 - Widyanti, Perdaning; Lestari, Puji; Ahmad, Prayudi (Jurnal Pekommas, 2024)
This research aims to analyze the influence of organizational communication climate and work meaningfulness on organizational commitment among educational staff at Universitas Negeri Yogyakarta. The hypotheses proposed in this study are that organizational communication climate and work meaningfulness have a partial and simultaneous effect on organizational commitment. The method used in this research is quantitative explanation, involving 366 members of the civil servant population. The data analysis method used in this study is regression analysis. The findings of this research indicate that organizational communication climate and work meaningfulness have a partial and simultaneous influence on organizational commitment. This research contributes to the study of organizational commitment among civil servants, which is influenced by organizational communication climate and work meaningfulness.